Fluconazole Disk Diffusion Test with Methylene Blue- and Glucose-Enriched Mueller-Hinton Agar for Determining Susceptibility of Candida Species - Lee, Sai-Cheong (American Society for Microbiology, 2001)
A 25-μg fluconazole disk diffusion test using a Mueller-Hinton agar plate containing 2% glucose and 5 μg of methylene blue/ml (GM-MH) was compared to the macrodilution reference method for 210 Candida species. The GM-MH agar plate was read at 24 h. The predictive values of disks with susceptible, intermediate, and resistant results on the GM-MH agar plate at 24 h were 97.1, 56.3, and 76.5%, respectively.